Investigation of genes coding for anti-HIV proteins MAP30 and MRK29 from Thai bitter melon (Momordica charantia L.) - Paktraporn Mekloy; Krisada Sakchaisri; Weena Jiratchariyakul; Somnuk Bunsupa (Pharmaceutical Sciences Asia, 2022)
Thai bitter melon, or Ma-Ra-Khee-Nok, is an M. charantia L. variety that is widely cultivated in Thailand. Thai bitter melon exhibits various pharmacological activities, including antidiabetic and antiviral. Many phytochemicals are found in various parts of this plant, notably ribosome-inactivating proteins (RIPs) in fruits and seeds. MAP30 is a well-known type I RIP isolated from seeds of the Chinese bitter melon. MAP30 exhibits various pharmacological activities, such as cytotoxicity and anti-HIV activity. However, there are no reports on MAP30 sequence information in Thai bitter melons. There have been only reported on MRK29 protein which exhibits anti-HIV reverse transcriptase activity, but only 20 amino acid sequences from the N-terminal were identified. In this study, we obtained 17 sequences with a high nucleotide sequence identity (>99%) with MAP30. Of these, one sequence (McRIP001) had double substitutions at the leading sequence, twelve partial (mature) sequences had an identity of 100%, and two sequences (McRIP002) had a single substitution (silent mutation) at the same position. Moreover, two sequences, McRIP003 and McRIP004, had a single substitution at different positions. Phylogenetic analysis of amino acid sequences demonstrated a close relationship between the obtained sequences and MAP30. Homology modelling revealed that the mutation points did not involve RNA N-glycosidase active sites. The cloning of MRK29 was unsuccessful due to the limit of available information. The present study provides a valuable reference for further research and quality control of healthcare products from Thai bitter melon.